DIMENSI RELIGIUS DALAM PEMBELAJARAN SAINS DAN TEKNOLOGI: Kasus Madrasah Aliyah Darul Ulum Jombang - Hartono Hartono (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
Modern science and technology is considered contributing to the transfer of positivism, materialism and belief of “The Death of the God.” However, factually this science and technology has become learning materials in madrasah. Therefore, it is found urgent learning science and technology on education Islamic perspective that reflects tawheed values or gratitude to God, or motivating people to be be thankful to God. It is the learning science and technology that do not exploit, instead cultivating, making use this nature for human walfare in order to develop the realization to God power on His all creatures. This learning science and technology “model” should be the centre of learning in madrasah (boarding school), so the expected competence students internalized is not only the mastery of knowledge (cognitive) but also gratitude to God (affective and psychomotor).